Vaccinium angustifolium (lowbush blueberry) leaf extract increases extravillous trophoblast cell migration and invasion in vitro. (29th January 2018) - Ly, Christina; Ferrier, Jonathan; Gaudet, Jeremiah; Yockell‐Lelièvre, Julien; Arnason, John Thor; Gruslin, Andrée; Bainbridge, Shannon
Abstract : Perturbations to extravillous trophoblast (EVT) cell migration and invasion are associated with the development of placenta‐mediated diseases. Phytochemicals found in the lowbush blueberry plant ( Vaccinium angustifolium ) have been shown to influence cell migration and invasion in models of tumorigenesis and noncancerous, healthy cells, however never in EVT cells. We hypothesized that the phenolic compounds present in V . angustifolium leaf extract promote trophoblast migration and invasion. Using the HTR‐8/SVneo human EVT cell line and Boyden chamber assays, the influence of V . angustifolium leaf extract (0 to 2 × 10 4 ng/ml) on trophoblast cell migration ( n = 4) and invasion ( n = 4) was determined. Cellular proliferation and viability were assessed using immunoreactivity to Ki67 ( n = 3) and trypan blue exclusion assays ( n = 3), respectively. At 20 ng/ml, V . angustifolium leaf extract increased HTR‐8/SVneo cell migration and invasion ( p < .01) and did not affect cell proliferation or viability. Chlorogenic acid was identified as a major phenolic compound of the leaf extract and the most active compound. Evidence from Western blot analysis ( n = 3) suggests that the effects of the leaf extract and chlorogenic acid on trophoblast migration and invasion are mediated through an adenosine monophosphate‐activated protein (AMP) kinase‐dependent mechanism. Further investigations examining the potential therapeutic applications of this natural health product extract and its major chemical compounds in the context of placenta‐mediated diseases are warranted.